Analysis of Potentials of Wave Power Plant for Fisherman Boats in Selayar Islands - Asri Anto; Luther Sule; Nasaruddin Azis (EPI International Journal of Engineering, 2020)
This research aims to determine the design of ocean wave power generation equipment for fishing boats in Selayar Islands and how much power is generated by ocean wave power generation equipment. The results showed that, the power generated with an arm length of 2 meters with a wave height of 0.1 - 0.6 meters adjusted to the ups and downs of the arms produced 71.7 W, 83.72 W, 168.28 respectively W, 240.4 W, 277.64 W and 483.2 W. Whereas an arm length of 4 meters with a wave height can reach 0.1 - 1 meter producing power of 35.76 W, 59.75 W, 72.24 W, 84.35 W, 144.51 W, 471.51 W, 596.64 W, 606 W, 642.83 W and 800.58 W.